2016
DOI: 10.1016/j.afos.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of sarcopenia and related factors in a community-dwelling elders Thai population

Abstract: BackgroundSarcopenia is one of common problems among elderly worldwide.ObjectivesSarcopenia is one of common problems among elderly worldwide. To determine the prevalence of sarcopenia and related factors in community-dwelling elders Thai population.MethodsThis cross-sectional study was performed in 243 subjects aged over 60 years. All participants were evaluated for handgrip strength by dynamometer and for gait speed by walking a 6-m distance. The muscle mass for subjects who had abnormal grip strength and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 30 publications
(40 reference statements)
4
36
4
3
Order By: Relevance
“…Fall history was acquired by asking participants the number of falls in the Statistical analysis. Based on a previous study 13 , the prevalence of sarcopenia in Thai community-dwelling elderly was 30.5%. Thus, the required sample for an α = 0.05 and Z = 1.96 was estimated to be 326 participants.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Fall history was acquired by asking participants the number of falls in the Statistical analysis. Based on a previous study 13 , the prevalence of sarcopenia in Thai community-dwelling elderly was 30.5%. Thus, the required sample for an α = 0.05 and Z = 1.96 was estimated to be 326 participants.…”
Section: Methodsmentioning
confidence: 98%
“…In order to effectively prevent the development of sarcopenia, it is important to know which risk factors contribute to the condition. Many factors have been identified to contribute to sarcopenia such as age, sex, physical activity, falls, frailty, comorbidities, body mass index (BMI), dietary intake, and malnutrition, however; this was not consistent across all studies 13,[18][19][20] . One of the reasons is that most of the previous studies did not clearly differentiate between primary and secondary sarcopenia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of sarcopenia in 1882 elderly Japanese individuals, aged 65 to 89 years, was observed to be 21.8% and 22.1% for men and women, respectively, with diagnosis based on the EWGSOP criteria [ 9 ]. Other research with 243 elderly Thai participants indicated a sarcopenia prevalence of 30.5% (33.9% for men and 29.3% for women) [ 10 ]. Few studies have reported the prevalence of sarcopenia based on the EWGSOP2 criteria.…”
Section: Sarcopeniamentioning
confidence: 99%
“…Sebuah studi di Thailand juga menyebutkan bahwa lansia madya lebih mengalami risiko terjadi sarkopenia (OR 6,19, IK 95% 2,91-13,18) dan begitu pula lansia tua (OR 15,47, IK 95% 4,93-58,54). 28 Status nutrisi adalah faktor dengan nilai OR terbesar pada analisis bivariat maupun multivariat. Hasil ini sesuai dengan penelitian komunitas lansia di Taiwan yang menunjukkan adanya asosiasi positif antara malnutrisi dengan sarkopenia (OR 2,859, IK 95% 1,133-7,217).…”
Section: Diskusiunclassified